Backpackers' Perception on Instagram Explore Indonesia Account: Persepsi Para Backpacker terhadap Akun Instagram Explore Indonesia - Krisna Yudha Pratama; Nur Maghfirah Aesthetika (Academia Open, 2024)
The rapid development of Instagram in Indonesia has catalyzed the swift emergence of creative industries, with consumers increasingly leveraging the platform for innovative purposes. This study employs the uses and gratification analysis method to dissect backpackers' perceptions of the Explore Indonesia Instagram account, focusing on its role as a reference for tourist destinations. Numerous travel accounts, including @exploreindonesia, @exploresidoarjo, @explorejogja, @yoikimalang, and @indoBackpackers, have flourished on the platform. The research reveals that @exploreindonesia has become a primary source of information and reference for backpackers, influencing their travel choices. This study aims to contribute valuable insights into the evolving dynamics of social media's impact on travel behavior, with implications for both researchers and industry professionals. Highlights : Instagram's Role: Examining the influential role of Instagram in shaping backpackers' perceptions and choices in the context of Indonesian tourism. Explore Indonesia Account: Investigating the @exploreindonesia Instagram account as a prominent reference and information source for backpackers seeking travel destinations. Uses and Gratification Analysis: Applying a methodological approach to understand how followers utilize Instagram as a reference for tourist destinations, emphasizing user autonomy and influence in the process. Keywords: Instagram, Backpackers, Explore Indonesia, Tourism, Uses and Gratification Analysis